Intestinal Microbiota of 6-week-old Infants Across Europe: Geographic Influence Beyond Delivery Mode, Breast-feeding, and Antibiotics - Fallani, M.; Young, D.; Scott, Jane; Norin, E.; Amarri, S.; Adam, R.; Aguilera, M.; Khanna, S.; Gil, A.; Edwards, C.; Dore, J. (Lippincott Williams & Wilkins, 2010)
Objectives: There are many differences in diet and lifestyle across Europe that may influence the development of the infant gut microbiota. This work aimed to assess the impact of geographic area, mode of delivery, feeding method, and antibiotic treatment on the fecal microbiota of infants from 5European countries with different lifestyle characteristics: Sweden, Scotland, Germany, Italy, and Spain.Patients and Methods: Fecal samples from 606 infants (age 6 weeks) recruited within the European project INFABIO were analyzed by fluorescent in situ hybridization combined with flow cytometry using a panel of 10 rRNA targeted group- and species-specific oligonucleotide probes. Information on factors potentially affecting gut microbiota composition was collected with questionnaires and associations were evaluated with multivariate analyses.Results: The Bifidobacterium genus was predominant (40% average proportion of total detectable bacteria), followed by Bacteroides (11.4%) and enterobacteria (7.5%). Northern European countries were associated with higher proportions of bifidobacteria in infant feces, whereas a more diverse microbiota with more bacteroides characterized southern countries. Bifidobacteria dominated the microbiota of breast-fed infants, whereas formula-fed babies had significantly higher proportions of Bacteroides and members of the Clostridium coccoides and Lactobacillus groups. Newborns delivered by cesarean section or from mothers treated with antibiotics perinatally had lower proportions of Bacteroides and members of the Atopobium cluster.Conclusions: Delivery mode and feeding method influenced the fecal microbiota of European infants at 6 weeks, as expected, but the effect of country of birth was more pronounced, with dominant fidobacteria in northern countries and greater early diversification in southern European countries.